The Dark Side of Things: Praxis of Curiosity in La silva curiosa (Julián de Medrano 1583) - Mercedes Alcalá Galán (Humanities)
Curiosity lies at the heart of the sixteenth-century miscellany books, which served as precursors to the essay genre. Among them, a truly exceptional piece stands out: La silva curiosa by Julián de Medrano, published in 1583. This work pushes the boundaries of curiosity to such an extent that it challenges its classification within the genre of miscellany owing to its unconventional and strange nature. Julián de Medrano, the author of this outlandish work, transforms himself into a character and protagonist, defining himself as an “extremely curious” individual. During his extensive travels, he curates a collection of “curious” epitaphs associated with often comical and peculiar deaths, spanning Latin, Spanish, Portuguese, French, Galician, and Italian. In addition to this, La silva curiosa includes an autobiographical narrative, a precursor to the Gothic genre, in which Medrano recounts unsettling encounters with black magic. This work offers a multifaceted exploration of curiosity, taking it to the extreme by narrating the author’s life experiences driven by a relentless pursuit of the curious, which is synonymous with the bizarre, extraordinary, marvelous, and unexpected. La silva curiosa emerges from a time marked by an almost nihilistic void, as the full force of the Baroque era has not yet arrived, and the ideals of humanism are fading away. It stands as a unique document that unveils an unexpected facet of the concept of curiosity within Spanish Renaissance culture.